Efficacy of a probiotic and chlorhexidine mouth rinses: A short-term clinical study - Harini P; Anegundi R (Wolters Kluwer Medknow Publications, 2010)
Introduction: Probiotic technology represents a breakthrough approach to maintaining oral health by utilizing natural beneficial bacteria commonly found in healthy mouths to provide a natural defense against those bacteria thought to be harmful to teeth and gums. However, data are still sparse on the probiotic action in the oral cavity. The review article on probiotics in children published by Twetman and Stecksen- Blicks in 2008 showed only one study of dental interest on probiotics in children. Aim and Objectives: The present study evaluated clinically the efficacy of a probiotic and chlorhexidine mouth rinses on plaque and gingival accumulation in children. The trial design is a double-blind parallel group, 14 days comparative study between a probiotic mouth rinse and a chlorhexidine mouth rinse, which included 45 healthy children in the age group of 6-8 years. Results: The Probiotic and Chlorhexidine groups had less plaque accumulations compared with the Control group at the end of 14 years (P < 0.001 and P < 0.001, respectively). But, unlike the plaque score, there was a significant difference in the Gingival Index between the Probiotic and the Chlorhexidine groups (P = 0.009), Probiotic group being better than the Chlorhexidine group (mean = 0.2300 and 0.6805, respectively). Conclusion: The Probiotic mouth rinse was found effective in reducing plaque accumulation and gingival inflammation. Therefore, probiotic mouth rinse obviously has a potential therapeutic value and further long-term study is recommended to determine its efficacy.